Pentecostalismo e Protestantismo “Histórico” no Brasil: um século de conflitos, assimilação e mudanças (Pentecostalism and “Historical” Protestantism in Brazil: one century of conflicts, assimilation and changes) - DOI: 10.5752/P.2175-5841.2011v9n22p504 - Campos, Leonildo Silveira (Horizonte, 2011)
This article proposes an analysis between Pentecostalism and “historical” Protestantism in the last century. Since 2010 there have been celebrations of the 100th anniversary of the establishment of Pentecostalism in Brazil, featuring renowned preachers such as the Italian-American Luis Francescon and Swedish Daniel Berg and Gunnar Vingren. Until the 1950s, the Christian Congregation in Brazil and Assembly of God, which resulted from the work of these three preachers, were the two major Pentecostal churches in Brazil. A new Pentecostal outbreak in the 1950s shook up the relations between Protestants and Pentecostal once again. Until then, Pentecostal churches centered their activities on divine healing and miracles. But in the last century, there was a process of intensification of the competition, conflicts, syncretism and complacency within the religious scenario, which accelerated after the 1970s, when a more competitive Pentecostalism started to advance. These neo-Pentecostals grew in numbers, and while expanding their symbolic universes, they incorporated symbols and beliefs, becoming the bearers of a hybrid and syncretic theology and rhetoric. What future can these successes and failures bring to Brazil’s religious field?